uPAR – uPA – PAI-1 interactions and signaling: A vascular biologist’s view - Binder, Bernd R.; Mihaly, Judit; Prager, Gerald W. (Thrombosis and Haemostasis, 2007)
The urokinase-type plasminogen activator (uPA), its inhibitor PA I-1 and its cellular receptor (uPAR), play a pivotal role in pericellular proteolysis. In addition, through their interactions with extracellular matrix proteins as well as with transmembrane receptors and other links to the intracellular signaling machinery, they modulate cell migration, cell-matrix interactions and signaling pathways. A large body of experimental evidence from in-vitro and in-vivo data as well as from the clinics indicates an important role of the uPA-uPAR-PAI-1 systems in cancer. In addition to their role in tumor cell biology, the uPA-uPAR-PAI-1 systems are also important for vascular biology by modulating angiogenesis and by altering migration of smooth muscle cells and fibrin deposition in atherosclerosis and restenosis. This review will focus on the general mechanism of uPAR/uPA/PAI-1 interactions and signaling and the possible relevance of this system in vascular biology.
Keywords: Urokinase / receptor; plasminogen activator inhibitors; angio-genesis and inhibitors; atherosclerosis; restenosis